MANAGEMENT OF PATIENTS WITH CERVICAL INSUFFICIENCY - S. A. Levakov; E. I. Borovkova; N. A. Sheshukova; I. M. Borovkov (Акушерство, гинекология и репродукция)
The article presents a literature review on methods of diagnosis, therapy and management of patients with isthmic-cervical insufficiency. Risk factors for the development of isthmic-cervical insufficiency are the acquired and congenital anomalies of the cervix. The diagnosis can be made only during pregnancy. Shortening of cervical length <25 mm before 24 weeks indicates the presence of ICN and the significant risk of miscarriage. Initial evaluation of the cervical length is from 14 weeks. When finding a shortening of the length of the closed part of the cervical canal is less than 25 mm the treatment of choice is surgical correction. When the cervical length more than 25 mm prophylactically from 19 to 32 weeks assigned to micronized progesterone 200 mg vagina. In identifying ICN after 24 weeks, the method of choice is the appointment of micronized progesterone and the installation of an unloading obstetric pessary. The use of a differentiated algorithm of management of patients with ICN reduces the chance of unexpected premature birth and neonatal morbidity and mortality.